2010
DOI: 10.1111/j.1469-7580.2010.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Germ layer differentiation during early hindgut and cloaca formation in rabbit and pig embryos

Abstract: Relative to recent advances in understanding molecular requirements for endoderm differentiation, the dynamics of germ layer morphology and the topographical distribution of molecular factors involved in endoderm formation at the caudal pole of the embryonic disc are still poorly defined. To discover common principles of mammalian germ layer development, pig and rabbit embryos at late gastrulation and early neurulation stages were analysed as species with a human-like embryonic disc morphology, using correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, a recent study of cynomolgus monkey embryos has indicated that nascent PGCs can emerge from the early amnion, which is an extra-embryonic membrane structure that subsequently surrounds the fetus (Sasaki et al, 2016). In primates, including humans, the amnion is formed from the pluripotent epiblast soon after implantation, albeit at a different time; this is not the case in pig and other mammalian embryos, in which the amnion develops after the initiation of gastrulation (Hassoun et al, 2010). In monkey embryos, WNT is expressed in the cytotrophoblast layer relatively close to the amnion, whereas the amnion itself is a source of BMP, indicating that there is an appropriate environment in this tissue for PGC specification (Sasaki et al, 2016).…”
Section: Signalling Principles Underlying Hpgc Specificationmentioning
confidence: 99%
“…However, a recent study of cynomolgus monkey embryos has indicated that nascent PGCs can emerge from the early amnion, which is an extra-embryonic membrane structure that subsequently surrounds the fetus (Sasaki et al, 2016). In primates, including humans, the amnion is formed from the pluripotent epiblast soon after implantation, albeit at a different time; this is not the case in pig and other mammalian embryos, in which the amnion develops after the initiation of gastrulation (Hassoun et al, 2010). In monkey embryos, WNT is expressed in the cytotrophoblast layer relatively close to the amnion, whereas the amnion itself is a source of BMP, indicating that there is an appropriate environment in this tissue for PGC specification (Sasaki et al, 2016).…”
Section: Signalling Principles Underlying Hpgc Specificationmentioning
confidence: 99%
“…Staging was carried out on dark‐field photographs after 2–3 hr of primary fixation. Early‐stage denominations of rabbit and pig embryos (Table ; Hassoun, Schwartz, Rath, Viebahn, & Männer, ) with their main developmental features (s. Blum et al, ; Viebahn, ) were used as a basis for scheduling allantois development in both species. Stage numbers were supplemented with + or ‐ to indicate advanced (i.e., Stage 8+) or early (i.e., Stage 9‐) substages.…”
Section: Methodsmentioning
confidence: 99%
“…Presence of the cloacal membrane at the bottom of the urogenital sinus has been shown in rabbits, pigs, and human embryos (29)(30)(31)(32)(33)(34). Kluth et al (35) also documented the presence of cloacal membrane at the ventral surface of the urethra in rats under SEM; however, they did not observe the fusion of urethral folds.…”
Section: Epithelial Cell Apoptosismentioning
confidence: 99%